12 The impact of maternal gestation hypertension and antihypertensive use on neonatal myocardial performance. (2nd February 2018) - Breatnach, CR; Monteith, C; McSweeney, L; Tully, EC; Malone, FD; Kent, E; Doherty, A; Franklin, O; EL-Khuffash, A
Abstract : Purpose: Assessment of myocardial performance in neonates using advanced techniques such as deformation imaging and rotational mechanics has gained considerable interest. Their applicability in elucidating abnormal myocardial performance in various clinical scenarios is becoming established. We hypothesise that infants born late preterm/term to mothers with gestational hypertension (GH) may have impaired left (LV) and right (RV) ventricular performance during the early neonatal period. We aimed to assess LV and RV function using echocardiography in infants born to mothers with GH and co. Methods: Term infants (>36+6 weeks) born to mothers with GH underwent assessment to measure biventricular function using ejection fraction (EF), deformation imaging, LV rotational mechanics [apical rotation, basal rotation, twist, twist rate an untwist rate], and RV-specific functional parameters [tricuspid annular plane systolic excursion (TAPSE) and fractional area change (FAC)] over the first 48 hours of age. A control group comprising infants born to healthy mothers was used for comparison. Results: Fifteen infants with maternal GH and 30 age matched controls were enrolled. GH infants exhibited no difference in birthweight, LV or RV length but had lower EF (54% vs. 61%, p<0.01), LV global longitudinal strain (−20% vs. −25%, p<0.01), and LV twist (11 o vs. 16 o, p=0.04). There were no differences in any of the RV functional parameters. Conclusion: Infants born to mothers with GH exhibit lower LV function when compared to healthy controls while RV function appears to be preserved. This relationship warrants further exploration in a larger cohort.